What Drives Banking Stability? Empirical Evidence from ECOWAS Countries (International Journal of Business, Economics and Management, 2017)
The study investigated the drivers of banking stability in ECOWAS countries. The results show that the stability in the banking sector is mainly influenced by the banking spread (Net Interest Margin-NIM). However, it finds that crises in the banking sector pose a negative influence on stability. In addition, the result reveals that high percentage of foreign banks reduces stability in the banking industry. The impact of income diversification has a positive influence on stability even though the effect is weak. Similarly, the impact of more concentrated banking industry on stability is positive but insignificant.